2019
DOI: 10.1016/j.afjem.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative awareness and experience with a ketamine-based anaesthesia package to support emergency and essential surgery when no anaesthetist is available

Abstract: Introduction Five of the 7.2 billion people on earth have limited access to emergency and essential surgical procedures. The lack of safe, affordable and timely anaesthesia services are primary barriers to universal surgical coverage. The objective of this study was to assess intraoperative awareness when the ‘Every Second Matters for Emergency and Essential Surgery – Ketamine’ (ESM-Ketamine) package was used to support emergency and essential surgeries and painful procedures in rural Kenya when n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Villegas and co-workers report a set of patients from rural Kenya, who underwent ketamine-based sedation or anaesthesia by non-anaesthetists. [13] In this study ketamine was shown to be safe in the doses used, with dreams the most commonly reported unusual experience during recovery and lower numbers of reported episodes of either awareness (almost 25%, mainly during procedural sedation) or pain. Most reported the recovery period as the worst part, but would recommend ketamine anaesthesia to other patients.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Villegas and co-workers report a set of patients from rural Kenya, who underwent ketamine-based sedation or anaesthesia by non-anaesthetists. [13] In this study ketamine was shown to be safe in the doses used, with dreams the most commonly reported unusual experience during recovery and lower numbers of reported episodes of either awareness (almost 25%, mainly during procedural sedation) or pain. Most reported the recovery period as the worst part, but would recommend ketamine anaesthesia to other patients.…”
mentioning
confidence: 65%
“…From a Nigerian ICU comes this report on the relative trauma-ICU burden and the fact that the burden from violence is an ever increasing one, despite the limited resources available for ICU care in many LMIC’s. [13] Trauma constituted a quarter of the ICU admission load, with bomb blast victims and gunshots comprising almost 25% of the trauma cohort. Many of these patients had burn injuries and these cases carried a mortality in excess of 80%, while the mortality for non-burned admissions was far lower.…”
mentioning
confidence: 99%
“…[9][10][11][12] Not all experiences of intraoperative awakening are the same or carry the same consequences: for the patient and the anesthesiologist, the most worrisome are those associated with having experienced pain during the intervention, since most patients who experienced pain suffer psychological sequelae, and the probability of developing PTSD appears to be closely related to previous experience of severe pain. [13][14][15][16] In the present investigation, what patients reported were voices and discomfort from the endotracheal had. In addition, longer-term surgeries and with more severe patients seem to be associated not only with a higher incidence of OID but also with a higher probability of developing PTSD.…”
Section: Discussionmentioning
confidence: 95%
“…OID is often the consequence of insufficient depth in the anesthetic technique used or the use of anesthetic drugs in doses lower than those actually required by the patient. [13][14][15][16] Likewise, there are a series of factors that condition its appearance, well related to the patient (sex, age, consumption of drugs, alcohol or psychotropic drugs, difficult airway, tolerance to the drugs administered, among others), with the type of surgical intervention ( urgent in patient, polytraumatized, cardiac surgery, obstetric anesthesia or procedures in neonates and children under 5 years old) or with the anesthetic technique (inhalation, total intravenous, use of neuromuscular relaxants, use of nitrous oxide, combined anesthesia or shallow anesthetic depth). 6,11,[17][18][19] As stated by Graham et al20, there are cases of patients with OID in which a predisposing cause could not be identified (up to 2.5% in some studies carried out) and even fraudulent claims (up to 4.2% in some series of cases of DIO).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation